2011
DOI: 10.1093/chemse/bjr102
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Impairment in an Adult Population: The Beaver Dam Offspring Study

Abstract: The objective of this study was to determine the prevalence of olfactory impairment and associated risk factors and the effects of olfactory impairment on dietary choices and quality of life. Odor identification was measured in 2838 participants aged 21-84 years (mean 49 years) in the Beaver Dam Offspring Study. The overall prevalence of olfactory impairment was 3.8%, increased with age (from 0.6% in those<35 years to 13.9% among those≥65 years) and was more common in men than women. In a multivariate model ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
210
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(225 citation statements)
references
References 30 publications
9
210
6
Order By: Relevance
“…It has been shown that men tend to have a poorer olfactory function than women, and the odds of men developing olfactory dysfunction were more than double compared with women [2,14,15]. In the present study, men also showed a higher prevalence of olfactory impairment (n = 23, 51%) than women (n = 13, 29%) even though our patient sample population was smaller.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…It has been shown that men tend to have a poorer olfactory function than women, and the odds of men developing olfactory dysfunction were more than double compared with women [2,14,15]. In the present study, men also showed a higher prevalence of olfactory impairment (n = 23, 51%) than women (n = 13, 29%) even though our patient sample population was smaller.…”
Section: Discussioncontrasting
confidence: 55%
“…Nutrition is an important element of health in the geriatric population, and some studies have reported that it can be influenced by diminished senses of smell and taste [21,22]. Whereas, other studies have reported that olfactory dysfunction was not associated with nutritional status [12,15,23]. In our study, nutritional status was evaluated by MNA score, BMI, and serum total protein and albumin level.…”
Section: Discussionmentioning
confidence: 66%
“…However, our study has some noteworthy limitations. First, number of odorants in the SDOIT may limit the ability to detect small decrements in odor identification or to distinguish hyposmia (partial loss of smell) from anosmia (complete loss of smell) [31,32]. Second, dietary intake was self-reported using FFQs which are known to underestimate energy intake and overestimate fruit, vegetable, and dairy intakes [33].…”
Section: Discussionmentioning
confidence: 99%
“…In 34 individuals cognitively intact prior to death, the extent of AD pathology at autopsy in central olfactory structures correlated significantly with the results on the Brief Smell Identification Test, a simple test of olfaction, suggesting that olfactory testing might help detect preclinical disease [14]. However, olfactory impairment is common in the elderly [15][16][17][18], and may arise as a consequence of diverse disorders of the nose, sinuses, or brain. Lack of specificity for AD is, therefore, an important limitation of olfactory testing, especially when the results are interpreted in isolation.…”
Section: Introductionmentioning
confidence: 94%